Psychological First Aid (PFA) untuk Perempuan Korban Kekerasan Seksual - Sanjani, Resi Raf (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Sexual harassment is a serious problem that all girls and women are facing this day. overall, 35% of women worldwide have experienced either physical and/or sexual intimate partner violence or non- partner sexual violence. In Indonesia itself, violence against women is became more complex and increasingly diverse. With 406.178 violence against women’s cases, this number increased from 2018 by 14%. Women who have been physically or sexually abused by their partners report higher rates of a number of important health problems. women who have experienced this form of violence are 2.3 times more likely to have alcohol use disorders and 2.6 times more likely to experience depression or anxiety. A victim of sexual assault may feel fear, worthlessness or numbing in the short term after the incident. In the long term, she may experience depression, chronic anxiety, suicidal tendencies or posttraumatic stress disorder. it is important for the victim to begin the process of healing as soon as possible. Psychological First Aid (PFA)—describes a humane, supportive response to a fellow human being who is suffering and who may need support—should be given in the immediate aftermath of rape or sexual assault. PFA can help ensure safety, calm, connectedness, hope and selfefficacy. The three basic action principles of PFA are look, listen and link. These action principles will help guide how the provider view and safely enter a crisis situation (sexual harassment), approach affected people and understand their needs, and link them with practical support and information.